PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP KINERJA GURU DI SMK AL-MUHTADIN DEPOK - Ramadhanti , Diah; Kurniawati, Dewi; Widyaningsih, Murti (JIMP : Jurnal Ilmiah Manajemen Pancasila, 2025)
This research aims to determine the influence of competence and training on the performance of teachers at SMK-Al Muhtadin Depok. Competence and training are two important factors that are believed to enhance teachers' performance in carrying out their professional duties. The method used in this research is a quantitative method with an associative approach. Data were obtained through the distribution of questionnaires to all teachers at SMK Al-Muhtadin Depok, and then analyzed using multiple linear regression. The research results indicate that competence has a positive and significant impact on teacher performance. Similarly, training significantly contributes positively to the improvement of teacher performance. Thus, it can be concluded that the simultaneous improvement of competence and training can drive the enhancement of teacher performance in the school environment. This research is expected to serve as input for school management in designing strategies to improve the quality of human resources.